Predictive value of contrast-enhanced carotid ultrasound features for stroke risk: a systematic review and meta-analysis - Zhou, Shili; Hui, Pinjing (Frontiers in Neurology, 2025)
ObjectiveTo elucidate the contrast-enhanced ultrasound (CEUS) features of carotid artery plaques in patients who have experienced an ischemic stroke (IS).MethodsA computerized search was conducted in databases such as Pub-Med, EMSCO, and Ovid to identify studies reporting CEUS findings of carotid artery plaques. Patients were categorized as IS and non-IS based on clinical and radiological diagnosis, and the quantitative and semi-quantitative CEUS data were analyzed for differences between the two groups.ResultsAfter the computerized search, a total of 13 eligible studies, comprising 3,092 participants (1,953 with stroke), were included for analysis. IS patients exhibited significantly higher plaque enhancement intensity versus control group (SMD = 0.71, 95% CI: 0.32, 1.11). The positive rate of plaque enhancement within the plaques was significantly higher in IS patients versus non-IS patients (OR = 3.25, 95% CI: 1.86, 5.68). The sensitivity of hyperintense lesion-based diagnosis of stroke was 0.68 (95% CI: 0.54, 0.80), and the specificity was 0.61 (95% CI: 0.47, 0.73), with an area under the curve (AUC) of 0.697.ConclusionThere are significant differences in CEUS characteristics of carotid artery plaques between IS and non-IS patients. IS patients display markedly augmented plaque enhancement intensity and a higher rate of positive enhancement compared to non-stroke individuals. These noteworthy findings have critical implications in enhancing the accuracy of IS diagnosis and improving the stratification of stroke risk for patients.Systematic review registrationThis study is registered with the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY), 202540006.